Case report: a 3-year follow-up on nodal marginal zone lymphoma coexisting with disseminated Talaromyces marneffei infection in a non-endemic area - Yu, Xiping; Xu, Houyun; Zhou, Junjie; Zhu, Zhiqiang; Li, Baizhou (Frontiers in Oncology, 2025)
This case report presents the details of an elderly man in Zhejiang Province of China, who tested human immunodeficiency virus (HIV) negative and subsequently developed Nodal Marginal Zone Lymphoma (NMZL) along with T. marneffei disseminated infection. The study focuses on analyzing the distinct clinical symptoms and pathological manifestations in order to offer precise diagnosis and effective treatment for patients. A 76-year-old male patient was admitted to our hospital due to recurrent fever. An enhanced CT of the abdomen revealed bilateral renal and adrenal mass, along with multiple enlarged lymph nodes in the retroperitoneum. A chest un-enhanced CT showed flaky high-density shadows in the left lung, along with multiple enlarged lymph nodes in the lung hilar, mediastinal regions, and the left supraclavicular side. Subsequently, we conducted a biopsy of the left supraclavicular lymph node and confirmed the NMZL combined with T. marneffei infection. Over 3 years follow-up, there was no recurrence of T. marneffei infection and the lymphoma remained stable. Clinicians and pathologists should remain vigilant about the possibility of T.marneffei infection in non-prone areas. When encountering patients with unexplained fever, swollen lymph nodes, and multiple systems involvement, it is crucial to consider the possibility of lymphoma and fungal infections coexisting.